Recovery of the European asset management ten years after the financial crisis - Matušovičová, Monika (Array, 2019)
The article is analyzing the current situation of the European asset management after the financial crisis 2007-09 and compares the difference to the dot com bubble in 2000-03. It compares European assets under management with the global situation as well as European macroeconomic indicators including gross domestic product and employment. The analysis is supported by the comparison of reactions of the financial market and gross domestic product to dot com bubble and financial crisis. Results of the analysis show that the industry has fully recovered from the financial crisis with the European assets under management well above pre-crisis peak. Equity funds are nowadays the most preferred type of mutual fund in the Eurozone followed by bond funds. That points to increased and renewed risk appetite of investors after the crisis. In the end is the article supported by other important aspects of European asset management as changing monetary policies of European Central Bank and Federal Reserve.